STRATEGI KEPALA MADRASAH UNTUK MENINGKATKAN PARTISIPASI MASYARAKAT DALAM BIDANG PENDIDIKAN DI MTs MA’HAD ISLAMY KOTA PAYAKUMBUH - Dasrul Fauzi (IAIN Batusangkar, 2019)
The strategy of madrasah heads to increase public participation in the field of education is an important factor in determining education outcomes. The purpose of this study is: To find out the strategy of the head of the madrasah to increase public participation in the field of Education in MTs Ma'had Islamy Payakumbuh City. Knowing the factors that influence the Head of Madrasah to increase public participation in the field of Education in MTs Ma’had Islamy Payakumbuh City. This type of research is qualitative. Data sources used are primary data and secondary data. Data collection techniques through interviews, observation and documentation. The informants in this study consisted of principals, public relations officers, and teachers at MTs Ma'had Islamy Payakumbuh City. Data analysis techniques in this study use data reduction, data presentation and data verification. The research results obtained are by holding meetings and establishing relationships with parents, visits to students 'homes, correspondence, approaches through community leaders, publicity and madrasah socialization, holding madrasa exhibitions, taking student reports and parents' involvement in the process learning. The forms of community participation in the MTs Ma'had Islamy Payakumbuh City have been carried out including the participation of money and goods, labor and expertise participation, and mind participation. Factors influencing the madrasah chief's strategy in increasing community participation in MTs Ma'had Islamy Payakumbuh City are: Supporting factors which include the willingness and ability of individuals / communities, the opportunity of madrasas, high level of individual / community education, income or income from parents of students. The inhibiting factor is due to the location and access to madrasas that are quite far away, parents and the community who have their respective activities so it is difficult to take the time to attend the madrasa and lack of awareness of the surrounding environment and madrasas, services and appeals that are still limited because the lack of ability and intense communication between madrasa managers towards parents and the community.